Watermarking Techniques for Copyright Protection of Videos - Kothari, Ashish M.; Dwivedi, Vedvyas; Thanki, Rohit M. (Signals and Communication Technology, 2019)
The book provides copyright protection approaches for videos using watermarking. The various watermarking techniques using various transforms such as discrete cosine transform (DCT), discrete wavelet transform (DWT) and singular value decomposition (SVD) for videos are presented. The book also provides video watermarking approach using compressive sensing (CS) theory. The presented watermarking techniques are designed and implemented using color digital videos. The performance of the presented techniques is evaluated using Peak Signal to Noise Ratio (PSNR) and Normalized Correlation (NC).